The Role of the Innate Immune System in Alzheimer’s Disease and Frontotemporal Lobar Degeneration: An Eye on Microglia - Elisa Ridolfi; Cinzia Barone; Elio Scarpini; Daniela Galimberti (Clinical and Developmental Immunology)
In the last few years, genetic and biomolecular mechanisms at the basis of Alzheimer’s disease (AD) and frontotemporal lobar degeneration (FTLD) have been unraveled. A key role is played by microglia, which represent the immune effector cells in the central nervous system (CNS). They are extremely sensitive to the environmental changes in the brain and are activated in response to several pathologic events within the CNS, including altered neuronal function, infection, injury, and inflammation. While short-term microglial activity has generally a neuroprotective role, chronic activation has been implicated in the pathogenesis of neurodegenerative disorders, including AD and FTLD. In this framework, the purpose of this review is to give an overview of clinical features, genetics, and novel discoveries on biomolecular pathogenic mechanisms at the basis of these two neurodegenerative diseases and to outline current evidence regarding the role played by activated microglia in their pathogenesis.